Optimization of Weapon Management in the Warehouse of the Indonesian Defense University Using Web-Based QR Code Technology - Fadhil, Muhammad Fadhil; Putra, I Made Aditya Pradhana; Setyawan, Muhammad Iqbal; Herris, Fhatur Robby Tanzil; Zhafirah, Findi; Firdaus, Eryan Ahmad (Marqcha Institute, 2025)
This study aims to develop a weapon management system in the warehouse of the Indonesian Defense University using QR code-based technology integrated into a web application. This system is designed to address various challenges of conventional management, such as slow recording processes, human error, and data discrepancies, which frequently occur in weapon inventory management. QR code technology enables automated data entry, tracking, and reporting processes, enhancing efficiency, accuracy, and data security. The Agile methodology is applied in the development of this system, covering several stages, including planning, sprint development, iterative testing, and refinement. This system provides key features such as weapon recording using QR codes, student data management, weapon borrowing and returning, and inventory report generation. Testing results show that this system successfully minimizes recording errors and accelerates operational processes. This research significantly contributes to creating a professional, transparent, and accountable weapon warehouse management model, which can serve as a reference for the development of similar systems in other defense environments.